Exploring The Influence Of Emotional Intelligence, Adjustment, And Aggression On Academic Performance Among Bahraich District Secondary School Students (Journal of Namibian Studies : History Politics Culture, 2023)
With an emphasis on variations between rural and urban contexts, this research investigates the impact of emotional intelligence, adjustment, aggressiveness, and academic achievement among secondary school students in Bahraich District. Emotional intelligence, adjustment, and aggressiveness were measured using standardised instruments with a sample of 300 kids distributed equally between urban and rural schools. Data about academic success was culled from official school records. In order to determine the connections between these factors and academic performance, the study used a quantitative research strategy that included regression and correlation analyses. The results show a negative correlation between aggressiveness and academic success, and a positive correlation between emotional intelligence and better adjustment and greater academic performance. It is worth mentioning that these elements have different impacts on pupils in rural and urban areas. It is more pronounced among urban students that emotional intelligence is associated with better academic performance. These findings emphasise the need to address aggressive behaviour and promote emotional intelligence and adjustment skills in order to improve academic performance, especially in schools with a diverse student body. The study's overarching goal is to enhance academic achievement in a wide range of socio-environmental circumstances by recommending treatments that specifically target students' emotional and behavioural development.